2004
DOI: 10.3758/cabn.4.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Unimodal and crossmodal effects of endogenous attention to visual and auditory motion

Abstract: Three experiments were conducted examining unimodal and crossmodal effects of attention to motion. Horizontally moving sounds and dot patterns were presented and participants' task was to discriminate their motion speed or whether they were presented with a brief gap. In Experiments 1 and 2, stimuli of one modality and of one direction were presented with a higher probability (p = .7) than other stimuli. Sounds and dot patterns moving in the expected direction were discriminated faster than stimuli moving in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
2
22
2
Order By: Relevance
“…Although caution is warranted on the role of motion processes in mental number line search because they are supported by an association of processes in the VIPS, we suggest that these mechanisms may correspond to selective attention to motion (Beer & Röder, 2004Lewis, Beauchamp, & De Yoe, 2000;Hillyard & Anllo-Vento, 1998). If this process devoted to motion is what was altered by TMS, then a mechanism implying motion may, in turn, be operating on the mental number line.…”
Section: Discussionmentioning
confidence: 81%
“…Although caution is warranted on the role of motion processes in mental number line search because they are supported by an association of processes in the VIPS, we suggest that these mechanisms may correspond to selective attention to motion (Beer & Röder, 2004Lewis, Beauchamp, & De Yoe, 2000;Hillyard & Anllo-Vento, 1998). If this process devoted to motion is what was altered by TMS, then a mechanism implying motion may, in turn, be operating on the mental number line.…”
Section: Discussionmentioning
confidence: 81%
“…The use of headphones can induce an apparent spatial mismatch between the acoustic and visual stimuli. This lack of co-localization can reduce the perceptual integration benefit, and may hence influence the observed neural correlates (Beer and Roder, 2004, Frassinetti et al, 2002, Meyer et al, 2005, Rohe and Noppeney, 2016, Soto-Faraco et al, 2002). To complicate matters further, the influence of Audio-visual disparity on behavioural integration itself may be task dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Attention can facilitate the binding across modalities by amplifying co-occurring objects, but can also reduce the likelihood of integration in complex scenes by limiting the range of objects that are likely to be bound (Beer and Roder, 2004, Beer and Roder, 2005, Macaluso et al, 2016, Talsma et al, 2006, Talsma et al, 2010). We have recently reported that auxiliary multisensory effects, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations